2006
DOI: 10.1111/j.1467-9280.2006.01698.x
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial Distance and Mental Construal of Social Events

Abstract: Construal-level theory proposes that increasing the reported spatial distance of events leads individuals to represent the events by their central, abstract, global features (high-level construal) rather than by their peripheral, concrete, local features (low-level construal). Results of two experiments indicated that participants preferred to identify actions as ends rather than as means to a greater extent when these actions occurred at a spatially distant, as opposed to near, location (Study 1), and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
475
1
26

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 560 publications
(530 citation statements)
references
References 21 publications
28
475
1
26
Order By: Relevance
“…We then asked them to selfreport whether their overall thoughts were of a specific (i.e., concrete) or general (i.e., abstract) nature (1 p very specific; 7 p very general). This self-reported measure revealed that, consistent with prior research (e.g., Fujita et al 2006 ) when the open-ended responses were coded by two judges as concrete or abstract. Respondents in the near condition were more likely to have concrete versus abstract thoughts (65% concrete, 35% abstract) relative to those in the far condition (31% concrete, 69% abstract).…”
Section: Study 3: Geographical Distancesupporting
confidence: 50%
“…We then asked them to selfreport whether their overall thoughts were of a specific (i.e., concrete) or general (i.e., abstract) nature (1 p very specific; 7 p very general). This self-reported measure revealed that, consistent with prior research (e.g., Fujita et al 2006 ) when the open-ended responses were coded by two judges as concrete or abstract. Respondents in the near condition were more likely to have concrete versus abstract thoughts (65% concrete, 35% abstract) relative to those in the far condition (31% concrete, 69% abstract).…”
Section: Study 3: Geographical Distancesupporting
confidence: 50%
“…For example, "making a list" could be described as "writing things down" or "getting organized," respectively. By coding concrete identifications as 0 and abstract identifications as 1, we were able to calculate an abstract identification index for each participant by summing their scores (which ranged from 0 to 15, see Fujita, Henderson et al, 2006). Finally, participants indicated their age and gender to complete the study.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the relationship between distance and construal is posited to be bidirectional. Thus, not only do people describe distal events using more abstract language (Fujita, Henderson, Eng, Trope, & Liberman, 2006), but they also respond to manipulations of high-level construalthinking about abstract elements of an action -by expecting that the action will happen further in the future than when thinking about it concretely (Liberman, Trope, McCrea, & Sherman, 2007).…”
mentioning
confidence: 99%
“…Spatial distance indicates that individuals construe faraway things or events more abstractly and nearby things more concretely [30]. Studies on temporal distance have found that individuals represent events happening in the past or future abstractly compared to events happening in the immediate environment [32].…”
Section: Construal Level Theory (Clt) Of Psychological Distancementioning
confidence: 99%